2017
DOI: 10.1080/17429145.2017.1298851
|View full text |Cite
|
Sign up to set email alerts
|

RNA-seq analysis of the salt stress-induced transcripts in fast-growing bioenergy tree, Paulownia elongata

Abstract: Paulowina elongata is a fast-growing tree species is grown in different climates and types of soils. Environmental adaptability as well as high-yielding biomass make the P. elongata species an ideal candidate for biofuel production. High soil salinity is known to inhibit plant growth dramatically or leads to plant death. The purpose of this study was to characterize the salt-induced changes in the transcriptome of P. elongata. Transcriptome differences in response to salt stress were determined by RNA sequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Previous reports indicated that the overexpression of GDSL esterase lipases (GLIPs) could release fatty acids acting as hormone signal transduction molecules [ 73 ]. It has also been reported that excessive GLIPs exhibited improved salinity stress tolerance in Oryza sativa and Arabidopsis thaliana [ 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports indicated that the overexpression of GDSL esterase lipases (GLIPs) could release fatty acids acting as hormone signal transduction molecules [ 73 ]. It has also been reported that excessive GLIPs exhibited improved salinity stress tolerance in Oryza sativa and Arabidopsis thaliana [ 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is also reported that salicylic acid (SA) induced under salt stress leads to the overexpression of GDSL. The excessive GDSL can later release fatty acids involved in signal transduction and SA pathway, which eventually strengthens tolerance to salt stress (Jiang et al 2012; Naranjo et al 2006; Chaires et al 2017) .…”
Section: Discussionmentioning
confidence: 99%
“…Among these species, Paulownia elongata is a widely distributed tree native to Asia and known for its high adaptability and rapid growth rate (Chaires et al 2017). In addition, P. elongata is also highly tolerant to a wide variety of biotic and abiotic stresses (Chaires et al 2017). However, information on the genetic background of P. elongata remains scarce.…”
Section: Paulownia Elongata; Chloroplast Genome; Phylogeny Inferencementioning
confidence: 99%